Local Wisdom and Ecological Character Education of the Gumuk Indigenous People - Ariska, Fitri; Maharani , Septiana Dwiputri; Supartiningsih (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
This study examines the local wisdom of the Gumuk indigenous people in the context of ecological character education, exploring how traditional knowledge contributes to the development of ecological awareness, character formation, and the preservation of cultural values. Using a qualitative ethnographic approach, this research applies Koentjaraningrat’s theory of cultural forms to analyze how local wisdom manifests in ideas, social practices, and material expressions. Data were collected through in-depth interviews, participatory observation, and documentation. In the final section, this study links the findings to Yudi Latif’s concept of cultural character education, which emphasizes the importance of internalizing local cultural values as the basis for building national character. The results of the study show that the local wisdom of the Gumuk community plays a significant role in building ecological awareness, strengthening collective identity, and serving as cultural capital in confronting the challenges of modernity. This study offers the concept of cultural education as an alternative solution to maintain the sustainability of the ecological values and character of the Gumuk indigenous community amid existing social dynamics. This study contributes to the broader discourse on indigenous ecological education by providing an ethnographic model that integrates local wisdom, cultural practices, and moral values as a living system of ecological character formation, drawing on Koentjaraningrat’s theory of cultural forms and Yudi Latif’s concept of cultural education.